A Study on Deep Learning approach for Network Intrusion Detection - lakshmi, S. Venkata; Prabakaran, T.Edwin (International Journal of Computer Sciences and Engineering, 2025)
Deep learning is a part of the broader family of Machine Learning. It refers to learning multiple levels of representation and abstraction that helps to understand data such as images, sound and text. This paper aims at giving an overview of deep learning, its applications and an approach for Network Intrusion Detection. KDDCup dataset is used for Intrusion detection and a comparison of different deep learning techniques applied for Intrusion Detection is made. A special focus is given on Self taught learning using Sparse Coding and its usage in classification. Self taught learning (STL) is a machine learning framework for using unlabeled data in supervised classification tasks. It is a deep learning approach that comprises of two stages for the classification task. Initially, a good feature representation is learnt from a large collection of unlabeled data, called as Unsupervised Feature Learning (UFL). Finally, the learnt representation is applied to labeled data and then classification task is performed.